2019
DOI: 10.1111/1462-2920.14562
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of gene regulation by TfoX and TfoY among diverse Vibrio species

Abstract: Summary Bacteria of the genus Vibrio are common members of aquatic environments where they compete with other prokaryotes and defend themselves against grazing predators. A macromolecular protein complex called the type VI secretion system (T6SS) is used for both purposes. Previous research showed that the sole T6SS of the human pathogen V. cholerae is induced by extracellular (chitin) or intracellular (low c‐di‐GMP levels) cues and that these cues lead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 84 publications
(168 reference statements)
2
43
0
Order By: Relevance
“…6A). Similar to a previously published comparison, V. parahaemolyticus had a similar transformation frequency to V. cholerae (35). Because expression of both tfoX and qstR were sufficient to increase transformation frequency in DS40M4 in the absence of luxR , we hypothesized that expression of these two transcription factors might increase transformation frequency in other vibrios.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…6A). Similar to a previously published comparison, V. parahaemolyticus had a similar transformation frequency to V. cholerae (35). Because expression of both tfoX and qstR were sufficient to increase transformation frequency in DS40M4 in the absence of luxR , we hypothesized that expression of these two transcription factors might increase transformation frequency in other vibrios.…”
Section: Resultssupporting
confidence: 89%
“…The only BB120 gene known to be controlled by TfoX that responded with its induction was qstR , suggesting that TfoX might function in BB120 but perhaps at a reduced capability. This is in accordance with the finding that the V. fischeri tfoX is slightly decreased in the ability to cross-activate the qstR of V. cholerae (35). One additional possibility is that there is a regulatory feedback loop that downregulates transcription levels of structural genes in the absence of a functional pilus ( i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Homologues of TfoY, such as TfoX of V. cholerae, Sxy-1 of Haemophilus influenzae, and Sxy of E. coli are regulators of DNA uptake and natural transformation in their respective organisms [24,[33][34][35][36]. Prior studies have shown that TfoY does not control competency; TfoY is, however, an activator of motility in diverse Vibrio species and frequently controls T6SSdependent killing as well [24,37]. It is important to note that the stability of Sxy of E. coli is also dependent upon LonA, which suggests that LonA proteolysis of TfoX-like domain containing proteins may be a common regulatory mechanism in diverse bacterial species [33].…”
Section: Discussionmentioning
confidence: 99%
“…coli are regulators of DNA uptake and natural transformation in their respective organisms [ 24 , 33 36 ]. Prior studies have shown that TfoY does not control competency; TfoY is, however, an activator of motility in diverse Vibrio species and frequently controls T6SS-dependent killing as well [ 24 , 37 ]. It is important to note that the stability of Sxy of E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation